Impact Regional Autonomy in Improving Public Services Quality - Heru Rochmansjah (GoAcademica Research & Publishing, 2019)
Public service quality and many other aspects are still far from expectations, especially public autonomy. More government work needs to be done by finding more solutions, such as revitalization, reorganization, deregulation, and increasing the professionalism of officials and personnel involved in work, including rewards and sanctions for public services. This effort can be achieved when each unit works together, Which impacts the improvement of public service quality.